Features levels of steroid hormones in the blood of children with neuro dystonia before and after treatment of Magne-B6 - Svetlana Yur'yevna Marakhovskii; Tamara Ismailovna Dzhandarova; Vladimir Aleksandrovich Baturin (Наука. Инновации. Технологии)
The study of the content of steroid hormones in the blood of boys and girls aged 10-11 years diagnosed with cardiopsychoneurosis on cardial type before and after treatment of Magne-B6 in the conditions of the Provincial Children's Hospital on the basis of functional diagnostics department (Stavropol). It was found that the drug-Magne B6 had no significant effect on the level of cortisol in both boys and girls, who remained at significantly higher levels compared with the data obtained in children in the control group. Boys with neuro dystonia drug Magne-B6 contributed to higher concentrations of testosterone to its level in the control group of children without affecting the content of estradiol in the blood. Use of the drug Magne-B6 in girls with neuro dystonia resulted in a decrease in the level of estradiol and testosterone, but at the same time, their concentration in the blood remained at signiicantly higher levels compared with the data obtained in children in the control group.